2013
DOI: 10.1073/pnas.1310894110
|View full text |Cite
|
Sign up to set email alerts
|

Ether lipid generating enzyme AGPS alters the balance of structural and signaling lipids to fuel cancer pathogenicity

Abstract: Aberrant lipid metabolism is an established hallmark of cancer cells. In particular, ether lipid levels have been shown to be elevated in tumors, but their specific function in cancer remains elusive. We show here that the metabolic enzyme alkylglyceronephosphate synthase (AGPS), a critical step in the synthesis of ether lipids, is up-regulated across multiple types of aggressive human cancer cells and primary tumors. We demonstrate that ablation of AGPS in cancer cells results in reduced cell survival, cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
186
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(205 citation statements)
references
References 26 publications
(38 reference statements)
11
186
0
Order By: Relevance
“…Based on our present results, PLA/AT-3 may affect the oncogenic activity and/or intracellular localization of H-Ras by altering the membrane structure through the reduction in the content of ether-type lipids. It was also reported that aggressive cancer cells possess significantly higher levels of ether-type lipids than less aggressive counterparts (53). Aggressive cancer cells highly expressed ADHAPS, an enzyme involved in the biosynthesis of the ether-type lipids, and the transformation of less aggressive cancer cells with H-Ras up-regulated ADHAPS expression, leading to an increase in the levels of ether-type lipids.…”
Section: Discussionmentioning
confidence: 95%
“…Based on our present results, PLA/AT-3 may affect the oncogenic activity and/or intracellular localization of H-Ras by altering the membrane structure through the reduction in the content of ether-type lipids. It was also reported that aggressive cancer cells possess significantly higher levels of ether-type lipids than less aggressive counterparts (53). Aggressive cancer cells highly expressed ADHAPS, an enzyme involved in the biosynthesis of the ether-type lipids, and the transformation of less aggressive cancer cells with H-Ras up-regulated ADHAPS expression, leading to an increase in the levels of ether-type lipids.…”
Section: Discussionmentioning
confidence: 95%
“…Altered metabolic pathways in cancer cells may be attractive targets for anticancer therapy. For example, inhibition of alkylglycerone phosphate synthase (AGPS), a critical enzyme for ether lipid synthesis, results in impairments in cancer pathogenicity by reduction of ether lipids and alterations of fatty acid, eicosanoid, and glycerophospholipid metabolism [56]. Knockdown of CKB inhibits cell proliferation and induces apoptosis in ovarian cancer Skov3 cell line by decreasing glycolysis [57].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, alkylglyceronephosphate synthase (AGPS), an enzyme that catalyzes the critical step in ether lipids synthesis, is shown to up-regulate in multiple types of cancer cell and primary tumor. AGPS alters the balance of structural and signaling lipids to fuel cancer pathogenicity (Benjamin et al, 2013). Nonetheless, whether AGPS is involved in chemotherapy resistance has remained unclear.…”
Section: Introductionmentioning
confidence: 99%